Effects of hyperbaric oxygen therapy on distraction osteogenesis - (:unkn) unknown (HEALTH COMMUNICATIONS INC, 2007)
Investigators in the present study explored the effects of hyperbaric oxygen (HBO) therapy on distraction osteogenesis in a rabbit limb-lengthening model. HBO treatment was provided to participants in a small animal pressure chamber once a day during the latent period of distraction osteogenesis at 2.5 absolute atmospheres of pressure. Bone mineral density measurements were obtained through torsional testing. The control group received no HBO treatment. Animals were killed 8 wk postoperatively for biomechanical testing. There was a statistically significant increase in bone mineral density in the HBO group compared with that in the non-HBO group, but no statistically significant differences were observed between biomechanical parameters of the 2 groups. The investigators suggest that these results must be further studied through histologic examination to determine the stepwise effects of HBO during and after Collagen synthesis.
Keywords: hyperbaric oxygen treatment; distraction osteogenesis; torsional testing; lengthening; RABBITS; FRACTURE